An image guided small animal radiation therapy platform (SmART) to monitor glioblastoma progression and therapy response. Issue 3 (September 2015) - Yahyanejad, Sanaz; van Hoof, Stefan J.; Theys, Jan; Barbeau, Lydie M.O.; Granton, Patrick V.; Paesmans, Kim; Verhaegen, Frank; Vooijs, Marc
Abstract Background and purpose Glioblastoma multiforme is the most common malignant brain tumor. Standard treatment including surgery, radiotherapy and chemotherapy with temozolomide is not curative. There is a great need for in vitro and in vivo models closely mimicking clinical practice to ensure better translation of novel preclinical findings. Methods and materials A 3D spheroid model was established using the U87MG cell line. The efficacy of temozolomide, RT and combinations was assessed using growth delay assays. Orthotopic glioblastoma tumors were established, different radiation doses delivered based on micro-CT based treatment planning (SmART-plan) and dose volume histograms (DVH) were determined. Tumor growth was monitored using bioluminescent imaging. Results 3D spheroid cultures showed a dose-dependent growth delay upon single and combination treatments. Precise uniform radiation was achieved in all in vivo treatment groups at all doses tested, and DVHs showed accurate dose coverage in the planning target volume which resulted in tumor growth delay. Conclusion We demonstrate that 3D spheroid technology can be reliably used for treatment efficacy evaluation and that mimicking a clinical setting is also possible in small animals. Both these in vitro and in vivo techniques can be combined for clinically relevant testing of novel drugs combined with radiation.